2021
DOI: 10.1186/s12909-021-02928-w
|View full text |Cite
|
Sign up to set email alerts
|

The perspective of undergraduate dental students on web-based learning in pediatric dentistry during the COVID-19 pandemic: a Korean multicenter cross-sectional survey

Abstract: Background The COVID-19 pandemic changed the world and created a shift in the dental education program. This sudden change in the dental education program may have affected the academic standards of dental students. This study aimed to evaluate the overall satisfaction and effectiveness of online learning in pediatric dentistry of undergraduate dental students’ during the COVID-19 pandemic in South Korea. Methods An anonymous online survey was sent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
3
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 39 publications
1
23
3
3
Order By: Relevance
“…Unlike recently published studies, the most used online platform among the participants in our survey was Google Classroom, followed by Microsoft Teams. This finding contrasts with previous work where ZOOM was reported to be the most commonly used online platform (Al-Balas et al, 2020;Ahmed et al, 2021;Brar et al, 2021;Herr et al, 2021;Temash et al, 2021). Herr et al (2021) found that ZOOM was the most used platform among South Korean dental students (Herr et al, 2021).…”
Section: Discussioncontrasting
confidence: 96%
See 4 more Smart Citations
“…Unlike recently published studies, the most used online platform among the participants in our survey was Google Classroom, followed by Microsoft Teams. This finding contrasts with previous work where ZOOM was reported to be the most commonly used online platform (Al-Balas et al, 2020;Ahmed et al, 2021;Brar et al, 2021;Herr et al, 2021;Temash et al, 2021). Herr et al (2021) found that ZOOM was the most used platform among South Korean dental students (Herr et al, 2021).…”
Section: Discussioncontrasting
confidence: 96%
“…This finding contrasts with previous work where ZOOM was reported to be the most commonly used online platform (Al-Balas et al, 2020;Ahmed et al, 2021;Brar et al, 2021;Herr et al, 2021;Temash et al, 2021). Herr et al (2021) found that ZOOM was the most used platform among South Korean dental students (Herr et al, 2021). We hypothesize two reasons for the differences.…”
Section: Discussioncontrasting
confidence: 96%
See 3 more Smart Citations